Introduction and Application of the Interferon-γ Assay in the National Bovine Tuberculosis Control Program in South Korea - Jang, Yun-Ho; Kim, Tae-woon; Jeong, Min Kyu; Seo, Yoon Jeong; Ryoo, Soyoon; Park, Chan Ho; Kang, Sin seok; Lee, Young Ju; Yoon, Soon-Seek; Kim, Jae Myung (Frontiers in Veterinary Science, 2020)
Bovine tuberculosis is a chronic disease impacting both public health and the livestock industry. The interferon (IFN)-γ assay has been introduced as an ancillary test for diagnosing bovine tuberculosis to overcome limitations of the skin test. The objective of this study was to assess the IFN-γ assay in terms of diagnostics and as a nationwide surveillance program in South Korea. From 2012 to 2013, cattle (n = 120) with bovine tuberculosis and cattle (n = 426) from bovine tuberculosis free herds were subjected to the IFN-γ assay to evaluate the sensitivity and specificity of the assay, respectively, depending on various cut-offs (0-3.5). When optical density of the cut-off was 0.1, the sensitivity and specificity were found to be 81.7% (74.7-88.6) and 99.5% (98.9-100.0), respectively. After introducing the IFN-γ assay as part of the national control program, the IFN-γ assay and single caudal fold skin test data were collected from 47 regional veterinary services to compare the results of these two tests. Overall, the agreement between the IFN-γ assay and the single caudal fold skin test (n = 492,068) was 98.2%, and Cohen’s kappa value for the two methods was 0.47. Serial and parallel use of the IFN-γ assay and skin test for the bovine tuberculosis control program were compared using samples (n = 91) from cattle confirmed as bovine tuberculosis positive in laboratories from 2014 to 2016. Parallel screening for bTB showed much higher sensitivity (86/91, 94.5%) than the following screening approaches: serial (47.2%, 43/91), single screening using CFT (63.7%, 58/91), or the IFN-γ assay (78.0%, 71/91). These results indicate that the IFN-γ assay and single caudal fold skin test are complementary to each other; therefore, parallel use of these two tests is considered a useful approach to reduce the prevalence of bovine tuberculosis in South Korea.